Comprehensive study on manifestation, management and outcome of post COVID rhino orbito cerebral mucormycosis in our institution - R., Shanthimalar; S., Muthuchitra; S., Mary Nirmala; P., Thamizharasan; G., Udhayachandrika; C., Balaji; S. P., Indu; P., Kousalya; A., Senthoorani; E., Yuvaraj (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Rhino orbital mucor mycosis in covid infected patients presented a challenge in management. We tried analysing comprehensively the manifestations and management and prognosis of post COVID rhino orbito cerebral mucormycosis (ROCM) patients in our institution. Patients with symptoms of ROCM were managed according to the guidelines issued by the directorate of medical education, Tamil Nadu, India. 30 possible ROCM patients were treated so far from May 2021. Patients underwent radiological, microbiological and pathological investigation. In stage 1, nasal cavity alone was involved in 11 patients. In stage 2, paranasal sinus extension was seen in 8 patients. In stage 3, orbital extension was seen in 10 patients. In stage 4, intra cranial extension was seen in 1 patient. 10 patients were probable ROCM without microbiological or pathological evidence. 20 patients had proven ROCM. They were treated with endoscopic debridement. Out of them 10 patients had to undergo orbital decompression and 5 of them had improvement in vision. All proven ROCM patients were treated with 3 weeks of injection liposomal amphotericin B along with oral posaconazole 300 mg for 3-6 weeks. Post-operative histopathology noted fungal invasion of blood vessels in 19 cases and thrombus in 10 cases of orbital involvement. No mortality was reported in the study group. COVID variant associated thrombosis may be the reason for increased incidence of mucor mycosis in post COVID patients. Team work, appropriate guidelines and adequate supply of medications helped in achieving desired outcome.